A correlation analysis of sacrococcygeal chordoma imaging and clinical characteristics with the prognostic factors - Zhao, Fei; Tian, Shujian; Zheng, Lei; Li, Yue; Zhang, Lu; Gao, Song (Frontiers in Oncology, 2022)
Objective To investigate the imaging and clinical risk factors related to the postoperative recurrence of sacrococcygeal chordoma. Methods 63 patients of sacrococcygeal chordoma proved by operation and pathology in our hospital from January 2009 to December 2019 were retrospectively analyzed in the related factors of imaging manifestations, pathological type, and extent of surgical resection. The recurrence of sacrococcygeal chordoma was followed up. Univariate Kaplan-Meier survival analysis and multivariate Cox regression analysis were used to analyze the related factors of recurrence. Results On plain radiographs and CT scans, chordoma primarily manifested as osteolytic bone loss and uneven soft tissue mass, with typical calcification or ossification (56.1 percent). Numerous chunk nodules with clearly high signal levels and short signal intervals were seen as the "pebble" in MRI characteristics on T2WI. The follow-up period ranged from 20 to 130 months, with a median time of 47.5 months. There were 14 recurrences (22. 2%) during the follow-up period. 13 patients with recurrence underwent surgery again, and 5 of them recurred after surgery (recurrence time range 3 to 97 months, median 38. 5 months). 6 (42.8%), 8 (57. 1%), and 13 (92. 9%) of the 14 patients with recurrence recurred within 2, 3, and 5 years after surgery, respectively. Univariate Kaplan-Meier survival analysis showed that occurred with local infiltration, Low differentiated chordoma, partial resection had a high postoperative recurrence rate, and all differences were statistically significant (P<0.05). Multi-factor Cox regression analysis showed whether local infiltration occurred and the degree of tumor resection were independent risk factors for tumor recurrence. Conclusion Sacrococcygeal chordoma has a high tendency of recurrence, and the likelihood of recurrence is higher in tumor occurred with local infiltration, non-complete tumor resection and low differentiated chordoma, which can be considered to shorten the review cycle and complete tumor resection as much as possible during surgery.